Upaya Penurunan Berat Badan dan IMT dengan Program Latihan Fisik Online pada Penderita Obesitas - Raharjo, Mutiara Amalia Fadzilla; Sugiarto, Sugiarto (Universitas Hamzanwadi, 2025)
Obesity, characterized by a Body Mass Index (BMI) >25 kg/m², is a major health problem caused by energy imbalance. This study aims to determine the effectiveness of an online physical exercise program in reducing weight and BMI in obese individuals. The method used is quantitative with a one-group pre-test post-test design. A total of 26 obese female clients from Company D were selected through purposive sampling. The intervention consisted of a progressive online exercise program at least 3 times/week for three months, with monitoring via a WhatsApp group. Data were analyzed using the Wilcoxon test. The results showed a significant decrease in weight and BMI (p < 0.05) each month. The average consecutive weight loss was -1.96 kg (month 1), -1.09 kg (month 2), and -0.44 kg (month 3). Meanwhile, BMI decreased by -0.80, -0.49, and -0.20. Discussion indicates that this program is effective, with the highest reduction occurring at the beginning due to physiological adaptation. The slowing trend indicates the need for a progressive strategy going forward. It is concluded that the online physical exercise program is effective in reducing weight and BMI in obese clients, although other factors such as diet need to be controlled in future studies.